Channeling Bo - Keady, G. L. (Gary L.) (Tuross Head, NSW : Big Island Publishing, 2023)
"In 1974, Bonnie Leigh, a young Australian, is tormented by inexplicable nightmares. Her worried father sends her to a psychiatrist, where she meets Dr Jackson Bolt. He discovers that Bonnie channels Queen Boudicca from 61 A.D. Through Bonnie's channelling, readers are transported to ancient Britain's epic battles."--Publisher.
Title from title screen.
Mode of Access: Available online.
Keywords: Historical fiction; Australian fiction; Historical fiction